Iran Economic Monitor, Fall 2017 : Sustaining Growth - The Challenge of Job Creation - World Bank Group (World Bank, Washington, DC, 2018)
The Iran Economic Monitor provides an update on key economic developments and policies over the past six months. It examines these economic developments and policies in a longer-term and global context, and assesses their implications for the outlook for the country. Its coverage has ranged from the macro-economy to financial markets to indicators of human welfare and development. This edition covers the economic growth of Iran for the year 2016. Growth performance in 2016 exceeded expectations based on the bounce back in oil production and exports. The economy registered a record growth rate of 13.4 percent according to the new GDP data published by the Central Bank of Iran. While Iran’s economy is relatively diversified for a resource-rich country, oil proceeds still play a crucial role in public finances and external accounts. Iran’s ability to increase production in 2016, despite the cuts agreed to by the rest of the OPEC members helped bring production near its pre-sanctions levels. The surge in exports led to an improvement in the current account surplus, to 3.9 percent of GDP in 2016, as growth in imports remained stagnant. Increased oil production and exports brought an increase in government revenues, however, the improvement was not enough to offset the widening expenditures; the fiscal deficit grew from 1.7 percent in 2015 to an estimated 2.2 percent in 2016. Creating fiscal space for growth will be important especially in view of the expected burden from securitization of government arrears and growing pension system liabilities. Iran managed to achieve single digit inflation in 2016, but inflationary pressures resurfaced towards the end of the year and in early 2017, as liquidity rose and the Iranian Rial continued to depreciate. Job creation remained limited. In the medium-term, the growth rates are expected to revert to an average of 4 percent, reflecting modest reintegration with the global economy in banking, trade and investment. There are significant downside risks, both domestic and external, to this moderate medium-term outlook.